Analysis of by high-throughput sequencing: Helicobacter pylori infection and salivary microbiome - Yingjie Ji; Xiao Liang; Hong Lu (BMC, 2020)
Abstracts Background There have been reports of Helicobacter pylori (H. pylori) in the oral cavity and it has been suggested that the oral cavity may be a reservoir for H. pylori reflux from the stomach. High-throughput sequencing was used to assess the structure and composition of oral microbiota communities in individuals with or without confirmed H. pylori infection. Methods Saliva samples were obtained from 34 H. pylori infected and 24 H. pylori uninfected subjects. Bacterial genomic DNA was extracted and examined by sequencing by amplification of the 16S rDNA V3-V4 hypervariable regions followed by bioinformatics analysis. Saliva sampling was repeated from 22 of the 34 H. pylori infected subjects 2 months after H. pylori eradication. Results High-quality sequences (2,812,659) clustered into 95,812 operational taxonomic units (OTUs; 97% identity). H. pylori was detected in the oral cavity in infected (12/34), uninfected (11/24) and eradicated (15/22) subjects by technique of high-throughput sequencing, occupying 0.0139% of the total sequences. Alpha diversity of H. pylori infected subjects was similar to that of uninfected subjects (Shannon: 1417.58 vs. 1393.60, p > 0.05, ACE: 1491.22 vs. 1465.97, p > 0.05, Chao 1: 1417.58 vs. 1393.60, p > 0.05, t-test). Eradication treatment decreased salivary bacterial diversity (Shannon, p = 0.015, ACE, p = 0.003, Chao 1, p = 0.002, t-test). Beta diversity analysis based on unweighted UniFrac distances showed that the salivary microbial community structure differed between H. pylori infected and uninfected subjects (PERMANOVAR, pseudo-F: 1.49, p = 0.033), as well as before and after H. pylori eradication (PERMANOVAR, pseudo-F: 3.34, p = 0.001). Using LEfSe analysis, 16 differentially abundant genera were defined between infected and uninfected subjects, 12 of which had a further alteration after successful eradication. Conclusions Our study using high-throughput sequencing showed that H. pylori was present commonly in the oral cavity with no clear relation to H. pylori infection of the stomach. Both H. pylori infection and eradication therapy caused alterations in community and structure of the oral microbiota. Trial registration clinicaltrials.gov, NCT03730766. Registered 2 Nov 2018 - Retrospectively registered, https://clinicaltrials.gov/ct2/show/ NCT03730766.